2020
DOI: 10.1051/mfreview/2020001
|View full text |Cite
|
Sign up to set email alerts
|

Weldability of S700MC steel welded with the hybrid plasma + MAG method

Abstract: The paper describes the microstructure of welded joints produced by the plasma+MAG (Metal Active Gas) method of S700MC high yield strength steel (700 MPa). Welded joints of thermomechanical steel have been made with different values of heat input. The results of metallographic research of welded joints, microstructure of the weld and heat affected zone, hardness distribution and impact toughness are presented. The heat affected zone consists of two sub-zones with different grain size and lowered hardness. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…The weldability of steels in the air environment is widely investigated. It has been shown that it depends on chemical composition, manufacturing method, and technological, metallurgical, and construction factors, and above all the welding technology [15][16][17]. Much less frequently mentioned is the subject of steels with yield strength higher than 420 MPa welded directly in the water.…”
Section: Introductionmentioning
confidence: 99%
“…The weldability of steels in the air environment is widely investigated. It has been shown that it depends on chemical composition, manufacturing method, and technological, metallurgical, and construction factors, and above all the welding technology [15][16][17]. Much less frequently mentioned is the subject of steels with yield strength higher than 420 MPa welded directly in the water.…”
Section: Introductionmentioning
confidence: 99%
“…As a method for improving the weldability of steel local heat treatment, provided by the heat from additional stitches, was chosen. Weldability tests are commonly used to evaluate the possibilities of the welding in the air for different materials [42,43], and in the water [35]. A Tekken weldability test was chosen for investigation.…”
Section: Introductionmentioning
confidence: 99%
“…These steels are also used in civil engineering. They have proved particularly useful in the production of the largest suspension bridges in the world, reducing the number of main supports and improving welding efficiency [11][12][13][14]. These steels are particularly suitable for the construction of buildings located in areas threatened by seismic shocks.…”
Section: Introductionmentioning
confidence: 99%